Pengaruh Performance Orientation, Learning Orientation, dan Trust in Supervisor terhadap Job Performance di Vosco Grup - Enggal, Pramesella Rezika; Anjaningrum, Widiya Dewi (Universitas Batanghari Jambi, 2024)
The cafÃ© business is currently mushrooming, causing business competition to become increasingly fierce and demanding high employee performance, including the Vosco Group, which is a well-known cafÃ© group in the city of Malang. The purpose of this research is to determine the influence of Performance Orientation, Learning Orientation, and Trust in Supervisor on employee Job Performance at Vosco Group. Through a study of all 51 Vosco Group employees, quantitative data from the results of distributing questionnaires was analyzed using SEM-PLS. The research results show that the influence of Performance Orientation is the strongest compared to Learning Orientation and Trust in Supervisor. However, the influence of these three factors is equally significant so it cannot be ignored.